Teachers as agents of change: a case study of action research for school improvement in Egypt - Kostandy, Mary Victor (AUC Knowledge Fountain, 2013)
This research focuses on conducting action research in collaboration with teachers in a private, international school in Egypt. It aims at empowering teachers as agents of changes through a process of developing school improvement plan. The research seeks mobilizing teachers and embarks on a case study of participatory action research for school improvement in Egypt, thus not only it contributes to literature in these areas but also represents a pioneering study in the Egyptian context. The researcher works in this school and is also a graduate of it. Thus her relationship with the school community extends over a period of 15 years. This has helped in building rapport between the researcher and the school practitioners. Similar to the researcher, 50% of the school teachers and administrators have been working in the school for over 10 years or are alumni of it. This in turn enabled the school to reserve its culture for decades. Aiming at supporting the school improvement, participatory action research is employed. The purpose of this action research is not only to gain knowledge but also to undertake actions, particularly by involving teachers in the reform process where their ownership of change evolves. The research followed qualitative approach and included emergent design of which regular meetings and focus group discussions were conducted with eleven teachers and surveys with open-ended questions were administrated to 68 teachers in order to assess the school performance and develop its improvement plan. In addition, the researcher used observation and kept a record of field notes. The research reveals the main areas of strength and improvement for the school. It also brought to life many of the concepts pertaining to the literature review such as democracy, reflection, positionality, trust, internal transformation, collaboration and resistance to change. These concepts have further been demonstrated in this research by mobilizing teachers as agents of change and sharing leadership responsibilities for the school improvement.